Interaction between DRD2 variation and sound environment on mood and emotion-related brain activity. (26th January 2017) - Quarto, T.; Fasano, M.C.; Taurisano, P.; Fazio, L.; Antonucci, L.A.; Gelao, B.; Romano, R.; Mancini, M.; Porcelli, A.; Masellis, R.; Pallesen, K.J.; Bertolino, A.; et al.
Highlights: DRD2 gene modifies music and noise effects on emotional brain activity. Mood changes after music or noise exposure are modulated by DRD2 gene. DRD2 GG subjects present better mood and decreased prefrontal activity after music. DRD2 GT subjects present worse mood and increased striatal activity after noise. Abstract: Sounds, like music and noise, are capable of reliably affecting individuals' mood and emotions. However, these effects are highly variable across individuals. A putative source of variability is genetic background. Here we explored the interaction between a functional polymorphism of the dopamine D2 receptor gene ( DRD2 rs1076560, G > T, previously associated with the relative expression of D2S/L isoforms) and sound environment on mood and emotion-related brain activity. Thirty-eight healthy subjects were genotyped for DRD2 rs1076560 (G/G = 26; G/T = 12) and underwent functional magnetic resonance imaging (fMRI) during performance of an implicit emotion-processing task while listening to music or noise. Individual variation in mood induction was assessed before and after the task. Results showed mood improvement after music exposure in DRD2 GG subjects and mood deterioration after noise exposure in GT subjects. Moreover, the music, as opposed to noise environment, decreased the striatal activity of GT subjects as well as the prefrontal activity of GG subjects while processing emotional faces. These findings suggest that genetic variability of dopamine receptors affects sound environment modulations of mood and emotion processing.